Perkembangan Keterampilan Sosial Emosional dan Pola Asuh Pada Sikap Manja Anak (Spoiled Child) (Studi Kasus Anak Usia 2-7 Tahun Pada Ibu yang Bekerja di Bank XYZ Suryopranoto Jakarta) - Elisabet Diana Sukianto (Jurnal Ketopong Pendidikan, 2022)
Working mothers often struggle to balance career demands and parenting, especially in early childhood. This study examines the link between social-emotional development and parenting patterns related to spoiled behavior in children aged 2–7 years, whose mothers work at Bank XYZ Suryopranoto Jakarta. Using a qualitative approach over seven months, data were collected through interviews, questionnaires, and observations with ten working mothers and their children. Findings show most mothers returned to work when their children were only three months old and spent 12–14 hours daily away from home due to commuting. Although children’s development was generally within the normal range, spoiled behavior appeared, especially when mothers were present. This was strongly linked to maternal guilt about leaving their children, which often resulted in overprotective or indulgent parenting practices. First-born children tended to display stronger social-emotional skills compared to younger siblings, though not universally. While many mothers attempted consistent discipline, feelings of guilt frequently undermined these efforts. The study concludes that maternal guilt is a major factor influencing spoiled behavior, highlighting the importance of consistent parenting strategies and adequate emotional support for working mothers to foster healthy child development.